Relevansi Konsep ‘Hamba Allah Bersaudara’ dalam Membangun Toleransi dan Keharmonisan dalam Pendidikan Islam - Busthomi, Yazidul; Damanhuri (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
Brotherhood can exist if it is based on the brotherhood of imaniyah, basyariyah, and wasathoniyah. Humans cannot live alone, apart from being personal creatures, humans are also social creatures. Brotherhood is an essential need. The faithful servants of Allah are brothers as explained in the Qur'an, surah Al-Hujurat verse 10, which means: verily the believers are brothers, therefore make peace between your two brothers and fear Allah so that you may receive mercy. And the Prophet Sallallahu 'alaihi Wasallam said: "Do not hate each other, envy each other, turn your back on each other, and be servants of Allah who are brothers, and it is not lawful for a Muslim to silence his brother for more than three days." (HR. Al-Bukhori). Brotherhood (ukhuwah) According to Quraish Shihab who refers to the Koran, there are 4 forms of brotherhood, namely (1) ukhuwah ubudiyah, (2) ukhuwah insaniyyah or (basyariyyah), (3) ukhuwah wathaniyah wa an-nasab, (4) ukhuwah fi ad-din al-Islam (brotherhood between fellow Muslims).